clınıcal EVALUATION OF FREE GINGIVAL GRAFT SHRINKAGE IN HORIZONTAL AND VERTICAL DIMENSIONS - Emine ÇİFCİBAŞI; Volkan KARABEY; Cenker KOYUNCUOĞLU; Ezgi DÜZAĞAÇ; Emrah GENCELİ; Kamber KASALI; Serdar ÇİNTAN (Journal of Istanbul University Faculty of Dentistry, 2015)
Purpose: To assess the shrinkage of Free Gingival Graft (FGG) in horizontal and vertical dimensions and calculate the changes in the surface area of the transplanted tissue in a 3 months period. Materials and Methods: A total of 30 FGG were placed aiming to increase attached gingiva around recession sites. Vertical recessions, horizontal recessions, surface area, plaque index, gingival index, periodontal probing depth and clinical attachment level were assesed at baseline, 1 and 3 months postoperatively. Results: Graft shrinkage between baseline and 1 month was more evident than 1 to 3 months in either dimensions. Both horizontal and vertical dimensions were significantly decreased (p<0.001) at 1 and 3 months post operatively. There was no significant change in PI and GI scores postoperatively compared to baseline (p>0.05). . Conclusion: The shrinkage of vertical and horizontal dimensions of the grafts were almost equal unlike the literature. In addition, the different dimensional changes observed in individual level deserve further research.